2018
DOI: 10.1002/jbm4.10061
|View full text |Cite
|
Sign up to set email alerts
|

Mucin 1 (Muc1) Deficiency in Female Mice Leads to Temporal Skeletal Changes During Aging

Abstract: Mucin1 (MUC1) encodes a glycoprotein that has been demonstrated to have important roles in cell‐cell interactions, cell‐matrix interactions, cell signaling, modulating tumor progression and metastasis, and providing physical protection to cells against pathogens. In this study, we investigated the bone phenotype in female C57BL/6 Muc1 null mice and the impact of the loss of Muc1 on osteoblasts and osteoclasts. We found that deletion of Muc1 results in reduced trabecular bone volume in 8‐week‐old mice compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Given the robust difference in TRP channel localization observed in vivo in kidney and duodenum, it is surprising that the measured parameters of Ca homeostasis – blood Ca 2+ , urine Ca excretion, PTH, and 1,25 (OH)2 vitamin D, are not more dramatically altered. Even the decrement in bone mineralization previously observed in Muc1 -/- mice is relatively minor compared to the decrease in bone density observed in TRPV5 -/- or TRPV6 -/- mice (20,21,25). All this suggests compensatory measures independent of these Ca 2+ -selective channels.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Given the robust difference in TRP channel localization observed in vivo in kidney and duodenum, it is surprising that the measured parameters of Ca homeostasis – blood Ca 2+ , urine Ca excretion, PTH, and 1,25 (OH)2 vitamin D, are not more dramatically altered. Even the decrement in bone mineralization previously observed in Muc1 -/- mice is relatively minor compared to the decrease in bone density observed in TRPV5 -/- or TRPV6 -/- mice (20,21,25). All this suggests compensatory measures independent of these Ca 2+ -selective channels.…”
Section: Discussionmentioning
confidence: 62%
“…This could reflect a state of Ca homeostasis, albeit with lower systemic Ca stores. 3) A previous study found mild reduction in bone density in Muc1 -/- mice (25). Osteoblast and osteoclast function appeared normal in Muc1 -/- mice, and no compelling mechanism for the bone phenotype was described.…”
Section: Discussionmentioning
confidence: 92%
“…[ 6 ] Mucin 1 (Muc1) expression increases during osteoblast differentiation when compared with undifferentiated human mesenchymal stromal cells, indicating a potential role for Mucin 1 in the dynamic bone formation and remodeling process. [ 7,8 ] Due to mucoadhesive properties of various polymers, [ 9,10 ] it is usually thought that mucin‐attractive polymers are capable of forming a large number of hydrogen bonds with mucin. [ 11 ] This might be because mucins contain hydroxyl groups in the branched sugar chains and carboxylic acid and sulfate groups in the terminal segments of branched chains., [ 12,13 ] Mucins typically contain 70–90 wt% carbohydrate, and the protein backbone accounts for most of the remaining part.…”
Section: Introductionmentioning
confidence: 99%
“…Mucin 1 (MUC1) is a transmembrane heterodimeric glycoprotein expressed on the surface of secretory epithelial, mucosal, and hematopoietic cells (Nath & Mukherjee, 2014). We previously found that MUC1 is upregulated in differentiating osteoblasts derived from human MSC and that Muc1 plays an age-dependent role in murine bone development (Brum et al, 2018). The extracellular domain of MUC1 (N-terminal) is composed of a variable number of 20 amino acid tandem repeats with extensive O-glycans (Dhar & McAuley, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the previously generated knowledge regarding the role of MUC1 in bone in vivo (Brum et al, 2018 ), there is a large knowledge gap as to how and what physiological changes in the ECM are modulated by MUC1 in human osteoblasts? Considering the upregulation of MUC1 under hypoxia and the oxygen concentration is a major modulating factor for ECM and its mineralization, we assessed the role of MUC1 and hypoxia on the proteomic composition of human osteoblast‐produced ECM and its consequences for osteogenesis and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%